Analisis Determinan Perdagangan Bilateral Indonesia Pendekatan Gravity Model - Dini Yuniarti (Economic Journal of Emerging Markets, 2007)
The objective of the study is analyzing determinants of Indonesian bilateral trade. This study using gravity model, which determinants of bilateral data e.a domestic income, population, distance, factor endowment, similarly size of economy, and dummy Regional Trade Arrangement, will be analyzed as well. The study uses data panel as a method.  Data comprise 10 main partners of Indonesian trade as cross section data. The observation comprise the period 1970-2000. The result concludes domestic income, population, similarly size of economy have positive impact on Indonesian bilateral trade, meanwhile distance have negative impact on Indonesian bilateral trade. Factor endowment and dummy Regional Trade Arrangement have no impact on Indonesian bilateral trade.Keywords: determinant, bilateral trade, gravity model